Optimalisasi Dokumen Administrasi oleh Mahasiswa Magang di Biro Pemerintahan dan Otonomi Daerah - Putriani Putriani; Emy Anggrainie; Rapel Rapel; Synthia Ferisca (Universitas Pahlawan Tuanku Tambusai, 2026)
The internship program provides students with the opportunity to gain direct work experience in government institutions. This activity was conducted at the Bureau of Government and Regional Autonomy, Regional Secretariat of Central Kalimantan Province from January 22 to May 22, 2026. The main problem identified was the lack of systematic document management and the absence of integrated data recording. The methods used include observation, documentation, and direct involvement in administrative activities. The solutions implemented were reorganizing administrative documents and creating a simple recording system using Microsoft Excel. The results show improved document organization and easier data retrieval. The impact includes increased administrative efficiency and better coordination in government activities.